Evaluation of the Potential of Metal–Organic Compounds ZIF-8 and F300 in a Membrane Filtration–Adsorption Process for the Removal of Antibiotics from Water - Daniel Polak; Szymon Kamocki; Maciej Szwast (Antibiotics, 2025)
Background/Objectives: Antibiotic contamination in water sources is a growing global concern, contributing to environmental degradation and the proliferation of antimicrobial resistance. Traditional treatment methods, such as advanced oxidation or high-pressure membrane processes, are often energy-intensive and economically unsustainable for large-scale or decentralized applications. This study explores the potential of two cost-effective, commercially available metal–organic frameworks (MOFs), ZIF-8 and F300, to improve the performance of membrane-based filtration–adsorption systems for removing tetracycline and sulfadiazine from water. Methods: Batch adsorption experiments were performed to evaluate the uptake capacities, kinetics, and isotherms of both MOFs toward the selected antibiotics. The membranes were modified using a low-cost silane-assisted deposition of MOF particles and tested in a microfiltration system. Removal efficiencies and water permeability were assessed and kinetic and isotherm models were applied to understand the adsorption mechanisms. Results: ZIF-8 showed superior adsorption performance, with maximum capacities of 442.2 mg/g for tetracycline and 219.3 mg/g for sulfadiazine. F300 was effective only for tetracycline. Membranes modified with ZIF-8 improved pharmaceutical removal by 187% (tetracycline) and 224% (sulfadiazine) compared to unmodified membranes. Although permeability decreased due to increased hydrophobicity, the materials and processes remained economically favorable. Conclusions: This study demonstrates that MOF-modified ceramic membranes, particularly those incorporating ZIF-8, offer a low-cost, scalable, and energy-efficient alternative for pharmaceutical removal from water. The approach combines strong environmental impact with economic viability, making it attractive for broader implementation in water treatment systems.